Membentuk Kesadaran Lingkungan Peserta Didik Melalui Program Pendidikan Lingkungan - Manappo, Yanti; Hunowu, Momy A (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
This research aims to investigate the role of education in shaping understanding of environmental issues. Awareness of the importance of environmental sustainability has become an increasingly serious concern today. Education is identified as the key to changing perspectives and actions towards the environment. This research will focus on how educational innovations shape environmental awareness and promote sustainable behaviors. The research method used is a qualitative approach with in-depth interviews with education stakeholders, teachers, and students involved in environmental education programs. Data will be analyzed to identify patterns in how education influences perceptions and environmental-related actions. The results of this research are expected to provide insights into the effectiveness of existing environmental education programs and how educational management can design new, more relevant, and impactful programs. This research will also contribute to understanding the role of education in addressing current and future environmental challenges. Thus, this research is expected to provide valuable input for education policies and educational management practices that focus on nurturing environmentally conscious citizens.